Use of maturity traits to identify optimal harvestable maturity of banana Musa AAB cv. “Embul” in dry zone of Sri Lanka - Kanchana, Senerath, A K; Thiruchchelvan, Kumara,A N (Open Agriculture 6: 143-151, 2021)
Banana is a climacteric fruit and perishable in nature having relatively high postharvest losses. Harvesting banana at a perfect maturity stage can reduce the quantity of losses during post-harvest handling. There is no identified optimal harvestable maturity time line available for local banana cultivars in Sri Lanka. Therefore, this study focused on use of maturity traits to identify optimal harvestable maturity for harvesting banana in the dry zone of Sri Lanka. Changes of fruit weight, length of banana fruits, fruit pulp weight, luminosity (L*), red-green (a*), yellow (b*), hue angle and chroma for skin of banana, total soluble solid (TSS) content, pH value and starch content of banana fruit pulp, respiration rate, and ethylene production of banana fruits during the developmental continuum were measured from seven days after flowering (DAF) to senescence. Data were statistically analyzed using one way-ANOVA at 95% confidence level. Results revealed that physical parameters such as length and weight of banana fruits were steadily increased in time. Chemical parameters such as TSS, pH and starch content of banana fruit pulp were significantly differed with the maturation. Fruit physiological parameters including ethylene production and respiration rate were significantly different with DAF. In conclusions, optimum maturity for the distant markets was observed in range of 77–84DAF. Maturity stage from 84 to 104DAF is better for the local/immediate consumption, and afterwards it can be recommended for the fruit processing firms.
Keywords: physical maturity; chemical parameters; physiological maturity; postharvest handling